Distance Estimation of the High-velocity Cloud Anti-center Shell - Wang, Yu-Ting; Liu, Chao; Zhang, Zhi-Yu (Research in astronomy and astrophysics, 2025)
High-velocity clouds (HVCs) are interstellar gas clouds whose velocities are incompatible with Galactic rotation. Since the first discovery of HVCs in 1963, their origins have been debated for decades but are still not settled down, because of the lack of vital parameters of HVCs, e.g., the distance. In this work, we determined the distance to the HVC, namely the Anti-center Shell (ACS). We trace the ACS with extinction derived from K-giant stars with known distances and with the diffuse interstellar band (DIB) feature at 5780 Å fitted on spectra of O- and B-type stars with distance. As a result, we provide a lower limit distance of ACS as ∼8 kpc, which extends the lower limit outward by approximately 4 kpc compared to previous work. A byproduct of the DIB method is that we detected a bar-shaped structure with an unusually high positive line-of-sight velocity. Its shape extends along the ( l ,  b ) = (155, −5)° sight-line and shows a slightly increasing trend in equivalent width and velocity as the distance increases.